Application of ZnO Nanoparticles EM Wave Detector Prepared by Solgel and Self-Combustion Techniques - Yahya, Noorhana; Daud, Hanita; Mohd Zaid, Hasnah; Shafie, Afza (Trans Tech Publications Ltd, Switzerland, 2010)
Zinc oxide (ZnO) has found many important applications such as optoelectronic devices,sensors and varistors. The challenging part however is synthesizing ZnO nanoparticles and its utilisation as EM detectors. Sol-gel and self-combustion techniques were chosen in this study due to the ability to produce single phase and nano-size samples. The starting mixture consists of 10 grams of zinc (II) nitrate, Zn(NO3)2.6H2O salt which was dissolved in 50 mL of nitric acid, HNO3.The solution was stirred at 250 rpm continuously for 1 day. The mixture was then gradually heated for every 15 minutes until it combusted at 110oC for the self-combustion technique. For the sol-gel technique, the dissolved mixture was heated at 40oC, 50oC, 60oC and 70oC until the gelatine was formed. After the drying process, the as-prepared samples were annealed at 100oC and 200 oC for 1 hour for each technique. Characterizations were performed by using X-Ray Diffraction (XRD), Raman Spectra and Scanning Electron Microscopy (SEM).The XRD analysis showed a major peak of [101] plane at 2Ө for the self-combustion technique and the sol-gel technique. Raman results for the samples prepared via sol-gel and self-combustion techniques had shown the major peak of ZnO that is located at the Raman shifts of 437.67 cm-1. Using the Scherrer equation, single crystal nano particle of ZnO was successfully obtained in the range of 38.49 nm to 50.70 nm for the sample prepared via the sol gel technique. By the self-combustion technique, the average dimension of the as-prepared sample is in the range of 34-49 nm. Further heat treatment resulted in a major change of the Raman shift corresponding to the single phase ZnO nano particles. The best samples were used as electromagnetic (EM) detectors. The EM detectors are polymer based composite which were prepared using a casting technique.